Earmarking Taxes Without Direct Returns: Accountability and Legal Compliance in the Management of Electricity PBJT - Nizar Zulkarnain (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Taxes are mandatory levies without direct returns to taxpayers. However, modern fiscal policy often uses earmarking, linking tax revenues to specific purposes. In Indonesia, the Certain Goods and Services Tax on Electricity allocates part of the revenue to public street lighting, raising issues of public accountability and legal compliance at the local government level. Objective: This study aims to examine how earmarking obligations under the Electricity PBJT reshape the management of public funds and to analyze their implications for accountability standards and legal compliance. Methods: The study adopts a qualitative approach based on normative analysis and policy document review, focusing on the legal framework and institutional design of regional fiscal policies. Results: The analysis shows that the allocation in the Electricity PBJT marks a paradigm shift from general revenue management to normatively bound revenue. This shift requires the internalization of allocation obligations in budget planning, which was previously not required. Allocated tax revenues must now be accounted for in a transparent and thematic manner, increasing the traceability and accountability of tax use. Conclusion: The placement of tax allocations in the Electricity PBJT increases transparency and traceability, without changing the character of the tax as a non-compensatory levy. The distinction between formal and substantive compliance is important for the effectiveness of earmarking, which depends on consistency of planning, budgeting, and oversight. Strict supervision and an integrated budgeting system are needed to ensure the success of this policy.